2004
DOI: 10.1016/j.ophtha.2003.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Autologous serum application in the treatment of neurotrophic keratopathy*1

Abstract: Autologous serum harbors neurotrophic factors. Autologous serum treatment may provide neural healers to the compromised ocular surface and seems promising for the restoration of the ocular surface epithelial integrity in patients with NK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
194
0
13

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(209 citation statements)
references
References 26 publications
2
194
0
13
Order By: Relevance
“…[1][2][3][4][5][6] Autologous serum has been found to contain vitamin A, epidermal growth factor, fibronectin, and transforming growth factor-b, which are important substances for corneal and conjunctival integrity. 3,4 However, autologous serum may be contraindicated or unavailable in infants, the elderly, patients with severe systemic bacterial infections or acute autoimmune disease, and those afraid of phlebotomy.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Autologous serum has been found to contain vitamin A, epidermal growth factor, fibronectin, and transforming growth factor-b, which are important substances for corneal and conjunctival integrity. 3,4 However, autologous serum may be contraindicated or unavailable in infants, the elderly, patients with severe systemic bacterial infections or acute autoimmune disease, and those afraid of phlebotomy.…”
Section: Introductionmentioning
confidence: 99%
“…The major contribution to trophism given by a AS eye drops may explain this, as it leads to a reduction of neurotrophic disease. Matsumoto et al showed that therapy with AS eye drops, thanks to nerve growth factor and surfactant proteins, can help in healing neurotropic keratopathy by facilitating nerve healing and epithelialization (49). This is also supported by investigations carried out by Lopez-Garcia et al (50).…”
Section: Semeraro Et Al: As Eye Drops In Sjögrenmentioning
confidence: 89%
“…9 Nerve growth factor is the bestknown neurotrophic factor; it is responsible for the growth and survival of developing neurons, and the maintenance of mature neurons. 10,11 Recent studies have indicated the efficacy of autologous serum in the treatment of neurotrophic keratopathy, osteoarthritis, chronic graft-versus-host disease and tympanic membrane perforations. [11][12][13] In addition to treatment, autologous serum should be able to prevent or at least decrease cell damage via its anti-apoptotic factors.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Recent studies have indicated the efficacy of autologous serum in the treatment of neurotrophic keratopathy, osteoarthritis, chronic graft-versus-host disease and tympanic membrane perforations. [11][12][13] In addition to treatment, autologous serum should be able to prevent or at least decrease cell damage via its anti-apoptotic factors. 14 It is these potentially beneficial substances that may provide medical benefits to diseased or damaged inner-ear cells and nerves, in a therapeutic and protective manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation